2022
DOI: 10.1038/s41598-022-05682-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cognitive impairment following chemotherapy treatment for breast cancer: a systematic review and meta-analysis

Abstract: Breast cancer survival rates have markedly improved. Consequently, survivorship issues have received increased attention. One common sequel of treatment is chemotherapy-induced cognitive impairment (CICI). CICI causes a range of impairments that can have a significant negative impact on quality of life. Knowledge of the prevalence of this condition is required to inform survivorship plans, and ensure adequate resource allocation and support is available for sufferers, hence a systematic review of prevalence da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 103 publications
3
39
0
Order By: Relevance
“…In fact, due to voluntarily enrollment in the study, our subjects' sample might be more aware of cognitive functioning and more cofounding variable might have a key role in explaining incidence of CRCI in our sample. But despite selection bias, our results are coherent with incidence of SCC in BC patients (Schimdt et al, 2016;Whittaker et al, 2022), indicating that CRCI is frequently present in breast oncological patients.…”
Section: Limitationssupporting
confidence: 80%
See 1 more Smart Citation
“…In fact, due to voluntarily enrollment in the study, our subjects' sample might be more aware of cognitive functioning and more cofounding variable might have a key role in explaining incidence of CRCI in our sample. But despite selection bias, our results are coherent with incidence of SCC in BC patients (Schimdt et al, 2016;Whittaker et al, 2022), indicating that CRCI is frequently present in breast oncological patients.…”
Section: Limitationssupporting
confidence: 80%
“…To date, the majority of CRCI research in patients with non-CNS cancer has involved women with breast cancer (BC), who represents approximately 43% of women cancer survivors in Italy ( Tagliabue et al, 2021 ). However, despite the vast literature regarding CRCI in BC patients, the prevalence estimates of subjective cognitive complaints (SCC) vary considerably between studies, ranging from 12% up to 86% ( Nelson and Suls, 2013 ; Janelsins et al, 2017 ; Whittaker et al, 2022 ). This lack of consensus regarding SCC cognitive decline in BC patients arises primarily due to methodological issues.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, an earlier study showed that short-term memory complaints are associated with cortical metabolism in cancer patients ( 17 ), not excluding metabolic changes as an acute compensatory mechanism. Moreover, several psychological measures have been shown to be related to cognitive complaints such as depression and anxiety ( 52 , 53 ), which could be interesting for further evaluation in the context of cerebral metabolism. Additionally, while fatigue is one of the most reported side effects of treatment for non-CNS cancer, associations between brain metabolism and fatigue have not yet been examined.…”
Section: Discussionmentioning
confidence: 99%
“…CICI occurring during and after chemotherapy has been found to be associated with neuronal damage, impaired mechanisms responsible for repair and remodelling of brain ( 9 ). CICI even persists for a longer period of time with more severe progressive manifestations after discontinuation of chemotherapy ( 10 ). CICI is recently becoming more widely recognized, therefore, early identification, aggressive and prompt medical interventions are required to prevent potentially high morbidity and mortality ( 11 ).…”
Section: Introductionmentioning
confidence: 99%